The influence of cross-cultural effect on Kérastase (L'oreal Group) consumer-brand relationship and engagement - Nobre, P. (2019)
Since their appearance, social media platforms (SMP) have attracted large amounts of users, many of whom have merged these networks into their daily life (Boyd and Ellison, 2007), which in consequence attract the interest of companies due to the potential to broadcast their marketing messages to their audiences (Cvijikj and Michahelles, 2013). In fact, SMP’s have changed the way consumers relate with brands, as they are no longer passive receivers of brand messages (Men andTsai, 2014). Today, consumers use technology to start conversations with brands, build connections, and are also able to generate digital content within online communities. For marketers, this new digital era reveals to be a challenge as they seek to leverage social media with relationship purposes, particularly keeping consumers engaged (Sklar, 2013). Additionally, global brands face an upper challenge as consumers’ cross-cultural context is highly determinant of their engagement. Having the above-mentioned scenario as starting point, how does this apply to luxury brands? This specific type of brands commonly has a “think global, act local” mindset. Nowadays, with the need of a social media marketing strategy that increase consumer-brand relationship and engagement, brands and marketers must understand not only the new and empowered consumer motivations but also what drive’s their engagement in a cross-cultural environment. Consequently, the aim of this research is to understand the influence of cross-cultural effect on consumer-brand relationship and engagement through social media platforms. Based on this, we purpose to answer to the following research questions: (i) is the level of engagement obtained by the content created by Kérastase on social media platforms affected differently according to culture? (ii) are there any differences between consumers of different cultures and their relationship to the different topics covered by luxury brands on their social media platforms?